A Treat to Touch:the Material Surface in Three Short Films by Carl Theodor Dreyer - Luke McFarlane (Opticon1826, 2011)
Much has been written on Dreyer’s cinematicvisual order and how his meticulously constructed sequences form from various elements an ordered whole. Edvin Kau, for instance, notes that ‘his films are a treasure house to explore for those who wish to learn about how meaning is articulated through the materials of the film medium’ and asserts how Dreyer’s ‘visual style’ comprises ‘cinematic spaces […] consciously formed’ to demonstrate the ‘psychological struggle’ taking place in characters such as Joan of Arc, in the 1928 La Passion de Jeanne d’Arc (Kau 2010, 1). These statements are never explained substantially enough for me. What meaning is this, within the context of a filmic medium? How precisely does this become psychological? Why should any of this matter enough to be termed a Dreyerian ‘visual style’? More needs to be said on what sort of compositional significance Dreyer masters, and what this can mean for the audience encountering his films.
Keywords: phenomenology; cinematorgraphy